TINGKAT PENGETAHUAN MASYARAKAT RW.IV KELURAHAN FONTEIN KOTA KUPANG TERHADAP PENGGUNAAN ANTIBIOTIK - NI NYOMAN YULIANI; CAROLINA WIJAYA; GERYANA MOEDA (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
do not know this and not taking antibiotics as directed. In Indonesia, misuse of antibiotics is supported by a number of sales of antibiotics which include hard drug classes freely. This study aims to look at the level of public knowledge about the use of antibiotics. This research is a descriptive study, the number of respondents A total of 100 respondents of the village RW.IV Fontein Kupang. All respondents were asked to fill in your ID and answer the questions in the questionnaire. Descriptive data shown in the frequency distribution. The results showed that 55% of respondents had a good knowledge level and 45% of respondents have a poor level of knowledge about the use of antibiotics.